Analysis of controlled ovarian hyperstimulation protocols in women over 35 years old with poor ovarian response: a real-world study - Xiaoyan Duan; Zhan Li; Mingming Li; Xing Ma (BMC, 2023)
Abstract The objective of this study was to investigate the optimal controlled ovarian hyperstimulation (COH) protocol for patients aged 35 and above with poor ovarian response (POR), utilizing real-world data. This retrospective cohort study examined clinical information from a total of 4256 patients between January 2017 and November 2022. The patients were categorized into three groups: modified GnRH agonist protocol (2116 patients), GnRH antagonist protocol (1628 patients), and Mild stimulation protocol (512 patients). Comparative analysis was conducted on clinical variables and pregnancy outcomes across the three groups. The GnRH agonist protocol was associated with a higher number of oocyte number (4.02 ± 2.25 vs. 3.15 ± 1.52 vs. 2.40 ± 1.26, p < 0.001), higher number of transferable embryos (1.73 ± 1.02 vs. 1.35 ± 1.22 vs. 1.10 ± 0.86, p = 0.016), higher cumulative live birth rate 28.50(603/2116) vs. 24.94(406/1628) vs. 20.51(105/512), p < 0.001) than GnRH antagonist protocol and Mild stimulation protocol, the Mild stimulation protocol was associated with a higher miscarriage rates 16.27(62/381) vs. 16.61(48/289) vs. 32.22(29/90), p = 0.001) than the other two groups. Therefore, it can be concluded that all three protocols can be used in patients over 35 years old with poor ovarian response. However, if patients require more frozen-thawed embryo transfers to achieve better cumulative live birth rates, the modified GnRH agonist protocol may be the preferable option.